Análise e estudo de luminotécnica para eficiência energética na UFERSA, Campus Caraúbas. - Melo, Cícero Eduardo de (Universidade Federal Rural do Semi-Árido, 2018)
The present research refers to the analysis and study of lighting for energy efficiency at UFERSA (campus Caraúbas), through the elaboration of an energy diagnosis, which deals with the technical and systematic analysis of a edification. In this way, the objective is to improve the energy performance of the institution. It is important to emphasize that the demand for electric energy in Brazil, grows surprisingly every year and, because of it, the need for new power plants for the additional generation of energy increases. Based on this need, the National Electric Energy Agency (ANEEL) has emphasized the importance of Energy Efficiency Programs (PEE) in order to reduce the excessive consumption of energy. As a result of this, a survey about the main factors of wastage of electric energy will be presented, and then will be elaborated in buildings I and II of classes and in the professor’s department I and II of UFERSA, the lighting design through the Lumens Method. From this, it will be verified whether the number of luminaires is adequate according to the dimensions and characteristics of the place.
Monografia
Keywords: Diagnóstico energético; Eficiência energética; Desperdício de energia; Dimensionamento luminotécnico; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA